Rozwiązane

Wykonaj działanie. Wynik podaj w najprostszej postaci:
a) [tex]\frac{9x^{2}-1 }{x^{2}+x } * \frac{(x+1)^{2} }{(x+1)(3x+1)} \\[/tex]

b) [tex]\frac{(x-3)(x+2)}{x^{2} } : \frac{(x^{2}-9)(x+1) }{(x^{2}+x)(x^{2} +3x) }[/tex]



Odpowiedź :

[tex]a) \ \frac{9x^{2}-1}{x^{2}+x}\cdot\frac{(x+1)^{2}}{(x+1)(3x+1)} =\frac{(3x+1)(3x-1)}{x(x+1)}\cdot\frac{(x+1)(x+1)}{(x+1)(3x+1)} = \frac{3x-1}{x}\\\\Zal: \ x \neq -1 \ \ i \ \ x\neq -\frac{1}{3} \ \ i \ \ x\neq 0[/tex]

[tex]b) \ \frac{(x-3)(x+2)}{x^{2}}:\frac{(x^{2}-9)(x+1)}{(x^{2}+x)(x^{2}+3x)} = \frac{(x-3)(x+2)}{x^{2}}:\frac{(x+3)(x-3)(x+1)}{x(x+1)\cdot x(x+3)} =\\\\\\= \frac{(x-3)(x+2)}{x^{2}}\cdot\frac{x^{2}(x+1)(x+3)}{(x+3)(x-3)(x+1)}=x+2\\\\\\Zal: \ x \neq -3 \ \ i \ \ x \neq -1 \ \ i \ \ x \neq 0 \ \ i \ \ x \neq 3[/tex]